The use of meta-research to evaluate the robustness of evidence in perinatal epidemiology - Giannakou, Konstantinos (Cyprus International Institute of Environmental and Public Health, Faculty of health Science, Cyprus University of Technology, 2018)
The volume of literature pertinent to healthcare is growing at an increasing rate with nearly one million articles on research involving human subjects are published each year. With the ever-increasing of published studies, scientists turn into systematic reviews and meta-analyses to summarize the evidence, using multiple related studies for a single research question. There are tens of thousands of systematic reviews already published, but their production is still increasing at a phenomenal rate. Even though systematic reviews have become a very popular type of research study that increased the scientific knowledge and inform clinical and policy decision making, their credibility is under threat as most appear to be either not useful or of uncertain utility. The problem is that the majority are unnecessary, inaccurate or misleading due to biases in the methodology and selective reporting of results, or they address questions that have no clinical value. The increase in the number of systematic reviews, along with escalating demand from policy makers for rapid reviews of research, has emerged an evolving scientific discipline, and a newer form of synthesis, umbrella reviews. An umbrella review is a new method that provide a comprehensive assessment of the body of information that is available on a given topic using the evidence from multiple systematic reviews and meta-analyses. This assessment is fundamental not only for understanding the reliability of an evidence-base but also serves as the foundation for clinical and public health recommendations.
Keywords: Literature pertinent; Healthcare